Peningkatan Hasil Belajar PKn Melalui Model Pembelajaran Picture And Picture Berbantuan Flash Card Siswa Kelas 2 SD Negeri Kenteng 01 - Nurvita, Senja Ayu; Slameto, Slameto; Setyaningtyas, Eunice Widyanti (Efektor, 2018)
Based on the facts conducted by researchers at SDN Kenteng 01 this problem arises is the lack of interest in students to the learning process by teaching teachers that still use conventional methods. The purpose of this research is to apply the learning model of image and flash-assisted image and improve student learning outcomes with collaboration model . This research was conducted in grade 2 with type of research of PTK spiral model which was proposed by C . Kemmis and Mc . Taggart In the study using 2 cycles of cycles I and II which consists of planning , step and reflection . Research data obtained from the test results and analyzed using descriptive techniques with the learning outcomes of Civics subjects on 2 cycles based on learning outcomes is ≥ 65 . The result of this research shows that there is an increase of learning result of Civics which can be seen on the value of learning result of Civics subject based on learning completeness that is cycle I is 66,77% and cycle II is 100%. Based on these results , this study has succeeded in improving student learning outcomes of Civics subjects.